Executive dysfunction and motor symptoms in Parkinson's disease Disfunções executivas e sintomas motores na doença de Parkinson - Indira Silveira Campos-Sousa; Raimundo Nonato Campos-Sousa; Luiz Ataíde Jr; Marta Maria de Brito Soares; Kelson James Almeida (Arquivos de Neuro-Psiquiatria)
The aim of this study is to analyze executive function and motor symptoms in patients with idiopathic Parkinson's disease (PD). The sample consisted of 44 subjects with PD between the ages of 45 to 75, who were examined consecutively. The subjects were divided into two groups according to the duration of the disease. The control group was composed of spouses, family and accompanying members. Patients included were submitted to motor dysfunction evaluation using the UPDRS. The executive functions modalities analyzed included: operational memory, inhibitory control, planning, cognitive flexibility and inductive reasoning. Significant differences between the experimental and control groups were found in all the executive domains studied. Evidence of tremor, rigidity and bradykinesia correlation with executive dysfunction were not observed. Patients with PD, even in the initial phase of the disease, presented executive dysfunction. The cardinal motor signs of the disease were not correlated with the cognitive dysfunction found. O objetivo do estudo é avaliar as funções executivas e sintomas motores em pacientes portadores de doença de Parkinson. A amostra se constituiu de 44 portadores de doença de Parkinson com idade entre 45 e 75 anos, examinados consecutivamente, os quais foram divididos em dois grupos de acordo com o tempo de duração da doença. O grupo controle foi composto de acompanhantes ou cônjuges. Os sujeitos selecionados foram submetidos à avaliação motora utilizando-se a escala UPDRS e à avaliação das funções executivas nas modalidades: raciocínio indutivo, memória operacional, controle inibitório, planejamento e flexibilidade cognitiva. Os resultados apontaram diferenças significantes entre os grupos experimentais e controle nas modalidades analisadas. Não encontramos evidência de associação entre tremor, rigidez e bradicinesia com as funções executivas. Conclui-se que os pacientes com doença de Parkinson, mesmo nas fases iniciais da doença, apresentam comprometimento cognitivo executivo. Os sintomas motores da doença não estavam correlacionados às disfunções executivas.